2019
DOI: 10.26499/wdprw.v47i2.356
|View full text |Cite
|
Sign up to set email alerts
|

Wujud Budaya Dan Nilai Pendidikan Dalam Cerita Rakyat Putri Jelumpang: Sebuah Kajian Antropologi Sastra

Abstract: This research is proposed to describe and explain; (1) the ideas (mentifact) in Putri Jelumpang folklore, (2) the character’s activities (sociofact) of Putri Jelumpang folklore, (3)  the cultural outcomes (artifact) in Put-ri Jelumpang folklore, (4) the education value of Putri Jelumpang folktale. This research used descriptive qualitative method with literary anthropology approach. Sampling technique use purposive sampling. Collecting data technique use document analysis and interview. To validity the data, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…To uncover the educative value of moral qualities, this research is relevant to Maulidiah and Saddhono (2019), who uncovered the educative value of moral ethics, the fulfillment of rights, and honesty in folklore Putri Jelumpang. In comparison, this research found educative value from Muhammad's characters as a speech partner in Quran, which is usable in both language ethics and moral education.…”
Section: Discussionmentioning
confidence: 99%
“…To uncover the educative value of moral qualities, this research is relevant to Maulidiah and Saddhono (2019), who uncovered the educative value of moral ethics, the fulfillment of rights, and honesty in folklore Putri Jelumpang. In comparison, this research found educative value from Muhammad's characters as a speech partner in Quran, which is usable in both language ethics and moral education.…”
Section: Discussionmentioning
confidence: 99%
“…While stories have animal-shaped characters and usually resemble human-like characters, Then Nurgiyantoro (2013) says that oral literature, in this case folklore, is part of folklore that lives, develops, and survives among the people who own it. Folklore is also a literary work that can provide appreciation and action about life values to readers or listeners (Maulidiah & Saddhono, 2019).…”
Section: Definition Of Folklorementioning
confidence: 99%
“…Sebagai bentuk pengembangan atau pembangunan ilmu pengetahuan, penelitian menempati posisi yang paling urgen dalam ilmu pengetahuan, yaitu untuk mengembangkan dan melindunginya dari kepunahan. Dalam posisi fungsi ini, penelitian memiliki kemampuan untuk meng-upgrade ilmu pengetahuan sehingga tetap up-to-date, canggih, applicated, dan aksiologis bagi masyarakat (Maulidiah & Saddhono, 2019). Selain itu, ilmu pengetahuan dengan sifatnya yang dinamis dan mengikuti perkembangan peradaban manusia tentu meniscayakan kehadiran fenomena baru berikut pengetahuanpengetahuan yang baru pula.…”
Section: Pendahuluanunclassified